Evaluation of early and late post-radiation reactions in patients with advanced cervical cancer treated with radiotherapy - Wareńczak-Florczak, Żaneta; Roszak, Andrzej; Bajon, Tomasz (Contemporary Oncology/Współczesna Onkologia, 2009)
Radiochemotherapy is acknowledged as a standard means of treatment in cervical cancer patients. However, there are some situations, for example general health condition or inap-propriate biochemical parameters, when we can use only radiotherapy. The present analysis included 90 patients with cervical cancer in IIB and IIIB according to FIGO. In this group 61 received radiochemotherapy (RCHT), and 29 patients received exclusively radiotherapy (RT). We evaluated early and late post-radiation reactions. Acute reactions were found in 46.6% and late toxicity was found in 23.3% of patients. Women treated with radiotherapy exclusively were significantly older than patients treated with radioche-motherapy, respectively 64.6±11.3 and 51.6±8.5 years (p<0.01). A higher percentage of acute side effects was observed in patients with RT than with RCHT (86.2% and 59%). Late post-radiation reactions also predominate in patients with RT (31% and 27.9%). The adverse effects were associated with prolonged time of treatment due to breaks in radiotherapy. A higher percentage of breaks was found in older patients, more frequently in patients with RT than in the RCHT group (37.9% and 21.3%). To conclude, early post-radiation reactions appeared more frequently than late post-radiation reactions. It was found that early and late post-radiation reactions appear more frequently in women treated with RT than RCHT, which was connected with their age (p < 0.001) and general health condition – they were not qualified for chemotherapy. Interruption in radiation delivery was longer than seven days in the group treated with RT, leading to prolongation of complete radiation treatment.